A Concept of Decision Making in Land Productivity: Combining Highest & Best Use and Analytic Network Process - Azizah, Urifatul; Utomo, Christiono (IPTEK Journal of Proceedings Series, 2019)
Understanding the concept of using the highest and best market is essential. Market forces will determine the creation of market value. To reach the equilibrium point, what the stakeholder wants is their desire is accep and provide optimal satisfaction (utility). To develop into a commercial property area it is necessary to analyse the most feasible and permitted land use permits, financially feasible and highest land productivity. Highest and best use (HBU) with feasibility requires interrelated criteria, therefore data and indirect consideration are required in additional research. Analytic Network Process (ANP) is a decision-making problem. It cannot be structured hierarchically because it leads to interaction and determines a higher level in the lower element. Not only are criteria that define alternatives as in hierarchy, but this is also an alternative can be important by using Analytic Network Process (ANP). This Paper is a conceptual based on literature review. A set of previous research are analysis to get the synthesis of the highest and best use (HBU) and the analytic network process (ANP) on land productivity decision making. A model is resulted to present the combination of four criteria of HBU into ANP